2012
DOI: 10.3390/ijerph9114033
|View full text |Cite
|
Sign up to set email alerts
|

Use of a Deuterated Internal Standard with Pyrolysis-GC/MS Dimeric Marker Analysis to Quantify Tire Tread Particles in the Environment

Abstract: Pyrolysis(pyr)-GC/MS analysis of characteristic thermal decomposition fragments has been previously used for qualitative fingerprinting of organic sources in environmental samples. A quantitative pyr-GC/MS method based on characteristic tire polymer pyrolysis products was developed for tread particle quantification in environmental matrices including soil, sediment, and air. The feasibility of quantitative pyr-GC/MS analysis of tread was confirmed in a method evaluation study using artificial soil spiked with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
67
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 115 publications
(81 citation statements)
references
References 52 publications
4
67
0
Order By: Relevance
“…15,17,19−21 In the case of the org-Zn marker, 22 recent research has shown that the dichloromethane extraction does not reliably exclude inorganic ZnO from partitioning from tread polymer into the solvent. 23 Inorganic Zn, while found in tread polymer, is also found in deicing salts, combustion exhaust, galvanized metal in automobiles, road barriers, fuel, oil, and brake linings, all of which can contribute to road runoff. 10,24−26 In one detailed study of an urban highway site with average daily traffic count of 150 000 vehicles, total zinc was found to be present primarily in the dissolved phase, 27 further suggesting that zinc-related markers are unlikely to be reliable markers for TRWP in the environment, despite the relatively high content of Zn in tread polymer (about 1%).…”
Section: ■ Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…15,17,19−21 In the case of the org-Zn marker, 22 recent research has shown that the dichloromethane extraction does not reliably exclude inorganic ZnO from partitioning from tread polymer into the solvent. 23 Inorganic Zn, while found in tread polymer, is also found in deicing salts, combustion exhaust, galvanized metal in automobiles, road barriers, fuel, oil, and brake linings, all of which can contribute to road runoff. 10,24−26 In one detailed study of an urban highway site with average daily traffic count of 150 000 vehicles, total zinc was found to be present primarily in the dissolved phase, 27 further suggesting that zinc-related markers are unlikely to be reliable markers for TRWP in the environment, despite the relatively high content of Zn in tread polymer (about 1%).…”
Section: ■ Introductionmentioning
confidence: 99%
“…5 Recently, a marker using pyrolysis products of tread polymers was developed for quantifying TRWP in environmental media. 23,28,29 In pyrolysis analysis, a sample is thermally decomposed under high temperature, and the characteristic fragments of tread polymers are quantified by a mass selective detector, such as gas chromatography−mass spectroscopy (GC/MS). This marker offers high specificity to tread, and stability in the environment due to high abundance of tread polymer in TRWP, which means that the marker will remain a component of TRWP during environmental transport; these characteristics were limited with previous markers used to measure tread in sediment.…”
Section: ■ Introductionmentioning
confidence: 99%
See 3 more Smart Citations